Abbess Piera de' Medici and her kin: gender, gifts, and patronage in Renaissance Florence. Issue 5 (16th December 2013) - Strocchia, Sharon T.
<x xml:space="preserve">Abstract</x> This essay advances our understanding of early Medici patronage by focusing on the intriguing figure of Piera de' Medici (c. 1400–1482), who matured into one of the most powerful abbesses in Renaissance Florence. As a religious woman, Piera used her ties to the city's ruling family to benefit her Vallombrosan community of S. Verdiana; in turn, it was through her agency that the Medici established long‐term claims on the convent, its consecrated virgins and its sacred cult. This case study shows how Piera combined rhetorical skills, political acumen and gift exchange to build a relationship with Giovanni de' Medici (1421–1463), whose patronage activities are less well known than those of other family members. It also invites a reconsideration of the role Florentine women played in producing visual culture by comparing Giovanni's donations to gifts made by his wife, Ginevra Alessandri. This perspective is especially valuable given that scholars have commented on the scarcity of female artistic patrons in fifteenth‐century Florence compared to other areas of Italy. By considering different classes of objects and models of exchange, this essay contends that Florentine women played a more expansive role in cultural production than previously recognized.